Influence of glass particle size on the physico-mechanical properties of red ceramic - Girondi Delaqua, Geovana Carla; Vernilli, Fernando; Teixeira, Silvio Rainho [UNESP]; Lopera Colorado, Henry Alonso; Monteiro, Sérgio Neves; Fontes Vieira, Carlos Maurício (Elsevier, 2023)
In this research, a study was carried out on the application of glass packaging in different granulometries in red ceramics. The raw materials underwent chemical, mineralogical, physical, dilatometric, thermal and microstructural characterization. Specimens were produced using a ceramic mass (0%) and incorporated up to 30% of glass waste in powder form, in granulometry 40, 100, 200 and 325 mesh. Specimens produced by uniaxial pressing (35 MPa) and fired at different temperatures (800–1050 °C). After firing, the properties of linear shrinkage, water absorption and flexural strength were evaluated. The microstructure was evaluated by optical microscopy. Analyzing the results, it is possible to observe that the raw materials have similar chemical composition and their application in ceramic materials is a highly viable option, and can also act as a flux, improving properties, in addition to reducing the firing temperature. The incorporation of waste reduced the water absorption and significantly increased the resistance of the pieces, mainly in the granulometry of 200 mesh and 325 mesh. In addition to improving the quality of red ceramics, incorporating glass from powder packaging is a highly advantageous alternative for recycling, as glass can take thousands of years to decompose in the environment.
Keywords: Ceramic; Glass; Post-consumer packaging; Waste